Windfall how the new energy abundance upends global politics and strengthens America's power - O'Sullivan, Meghan L. 1969- (Simon & Schuster, 2017)
The Harvard professor argues that fears of energy scarcity have resulted in energy abundance, and describes how new energy realities create a strategic environment to Americas advantage
Keywords: Sicherheitspolitik; Erneuerbare Energien; Außenpolitik; Einfluss; USA; World politics / 21st century; Power resources; World politics; World Politics / 1991-; Energy resources; 2000-2099